Identification of pathotype of Verticillium dahliae isolates on cotton in Zhejiang Province and phenotypic analysis on inhibitory effect by high temperature - SUN Xiaoting; LU Xiuyun; ZHANG Jingze; ZHU Shuijin (浙江大学学报. 农业与生命科学版)
China is the largest cotton producing country in the world. Zhejiang Province owned cotton growing area of about 17 264 hectares in 2013, was not major cotton producing area in China. Verticillium wilt, caused by Verticillium dahliae, is one of the most important disease of cotton and causes great economic losses in almost all cotton producing areas, but has not been found in fields in Zhejiang region. However, in 2014, the serious verticillium wilt disease of cotton was observed in the experimental field of Zhejiang University. The disease began to appear in the early June and occurred seriously in the early July. The disease caused the serious defoliation on the middle and lower parts of plants and the diseased plants were significantly dwarf. However, the disease became to remit gradually in the early August during high temperature in summer and dwarf phenomenon of the diseased plants was not obvious with new leaf formation. Since then, the diseased plants were still able to bloom and produce bolls. The symptom of the disease was similar to that caused by the defoliating pathotype strains of V. dahliae but in the later period, not identical to that.Based on the importance of verifying pathotype of pathogen and understanding the phenomenon of high temperature inhibiting disease for disease control, we detected the isolates causing the verticillium wilt disease of cotton by using the specific primers of defoliation and nondefoliation pathotypes of V. dahliae and characteristics of microsclerotia. Meanwhile, the effect of temperature on growth and development of pathogen was determined and the reason for the phenomenon of high temperature inhibiting disease was analyzed as well.Results of polymerase chain reaction (PCR) amplification using the specific primers showed that the isolates (VD-h1, VD-h2, VD-h6, VD-h3 and VD-h5) obtained all belonged to the defoliating pathotype. The results of observation for characters of microsclerotia formation confirmed that the difference of microsclerotia length-towidth ratio between defoliating and nondefoliating pathotype isolates was remarkable. Temperature had a significant influence on Verticillium isolates. The optimal growth temperature of two isolates (VD-h1 and VD-h6) from Zhejiang was 22-28℃ and two (VD-101 and VD-086) from Xinjiang was 22-26 ℃, whereas at 32 ℃, fungal hyphal growth was all inhibited. At the same time, the numbers of produced conidial decreased and conidial germination was delayed. Combining biological properties of fungus and meteorological data, research results indirectly verified that the reason for disappearance of disease symptoms was that the growth and reproduction of pathogen were inhibited under the condition of high temperature in summer. In sum, this study provides important scientific data for studying the regulation of disease occurrence in future.